The Effect of Employee Competency and Public Service Information System on Public Satisfaction with Public Service Effectiveness as an Intervening VariableiIt The Patumbak District Office - Arius Telaumbanua; Khairudin Tampubolon; Ratna Sari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
High-quality public services are an important indicator in achieving effective and responsive governance. However, several obstacles still occur in public service implementation, such as limited employee competence and the suboptimal utilization of public service information systems, which may affect service effectiveness and community satisfaction. Therefore, this study aims to analyze the influence of employee competence and public service information systems on community satisfaction with public service effectiveness as an intervening variable at the Patumbak Subdistrict Office. This research employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to 110 respondents who were service users, selected using the cluster sampling technique. Data analysis was conducted using multiple linear regression and path analysis to examine both direct and indirect relationships among the variables. The results show that employee competence has a positive and significant effect on community satisfaction with a t-value of 7.081 > 1.982 and a significance level of 0.001 < 0.05. Employee competence also significantly influences the effectiveness of public services with a t-value of 5.031 > 1.982. The public service information system significantly affects community satisfaction with a t-value of 5.475 > 1.982 and also influences public service effectiveness with a t-value of 5.304 > 1.982. Simultaneously, employee competence, public service information systems, and public service effectiveness significantly affect community satisfaction with an F-value of 45.524 > 2.69 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.563 indicates that the research variables explain 56.3% of the variance in community satisfaction. This study recommends improving employee competence and optimizing the utilization of public service information systems to enhance service effectiveness and community satisfaction.Keywords: Community Satisfaction, Employee Competence, Public Service Effectiveness, Public Service Information Systems.